BMC Infectious Diseases - Bhat, Rauf.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Infectious Diseases is an open access, peer-reviewed journal that considers articles on all aspects of the prevention, diagnosis and management of infectious and sexually transmitted diseases in humans and animals, as well as related molecular genetics, pathophysiology, and epidemiology. Topics include: Bacterial and Fungal Diseases Healthcare-Associated Infection Control Hepatitis and Co-Infections HIV and Co-Infections Parasitological Diseases Sexually Transmitted Diseases Tuberculosis and Other Mycobacterial Diseases Vaccines Viral Diseases As a BMC Series journal, BMC Infectious Diseases does not make editorial decisions based on the perceived interest or potential impact of a study. Manuscripts are considered for publication if they are scientifically valid. For research articles, this includes having a clearly defined and sound research question, appropriate methodology and analysis, and adherence to community-agreed standards relevant to the field. .
Keywords: Diseases; Parasitology; Medical microbiology; Tropical medicine; Internal medicine; Diseases; Parasitology; Medical Microbiology; Tropical Medicine; Internal Medicine